Evaluation of the Effectiveness of a Chronic Ocular Hypertension Mouse Model Induced by Intracameral Injection of Cross-Linking Hydrogel - Chen, Junjue; Sun, Jun; Yu, Huan; Huang, Ping; Zhong, Yisheng (Frontiers in Medicine, 2021)
Background: Glaucoma is an irreversible and blinding neurodegenerative disease that is characterized by progressive loss of retinal ganglion cells. The current animal models of glaucoma fail to provide a chronic elevated intraocular pressure and cannot maintain the optical media clarity for a long time, which brings some difficulties to the study of glaucoma. Here, we developed a new chronic ocular hypertension model of mice induced by cross-linking hydrogel intracameral injection. Methods: C57BL/6J mice aged 6–8 weeks were randomly divided into the control group and the operation group. The mice of the operation group were injected with cross-linking hydrogel to induce ocular hypertension. Intraocular pressure was measured preoperatively, 3 days after surgery, and weekly until the end of the study. Flash visual evoked potential (F-VEP) was used to observe optic nerve function at different times (preoperatively and 2, 4, and 6 weeks) after chronic ocular hypertension (COH). Retinal TNF-α, IL-1β, and IL-17A protein expression were measured by western blotting in the control group and in mice at 2, 4, and 6 weeks after COH. Microglial cell activation was evaluated by immunofluorescence staining and western blotting. Apoptosis and loss of retinal ganglion cells after 2, 4, and 6 weeks of intracameral injection of cross-linking hydrogel were observed by the TUNEL assay and Brn3a protein labeling. The loss of optic nerve axons in COH mice was evaluated by neurofilament heavy polypeptide protein labeling. Results: Intracameral injection of the cross-linking hydrogel induces increased intraocular pressure (IOP) to a mean value of 19.3 ± 4.1 mmHg, which was sustained for at least 8 weeks. A significant difference in IOP was noted between COH mice and sham-operation mice (p < 0.0001). The success rate was 75%. The average amplitude of F-VEP in mice with COH was reduced (p = 0.0149, 0.0012, and 0.0009 at 2, 4, and 6 weeks after COH vs. the control group, respectively), and the average latent period in mice with COH was longer (p = 0.0290, <0.0001, and <0.0001 at 2, 4, and 6 weeks after COH vs. the control group, respectively) compared with that in the control group. TNF-α, IL-1β, IL-17A, Iba-1, and CD68 protein expression increased in COH mice. During the processing of COH, the number of microglial cells increased along with cellular morphological changes of rounder bodies and thicker processes compared with the control group. Apoptosis of retinal ganglion cells (RGCs) was clearly observed in mice at 2, 4, and 6 weeks after COH (p = 0.0061, 0.0012, <0.0001, and 0.0371 at 2, 4, and 6 weeks after COH vs. the control group, respectively). The RGC density decreased significantly in the COH mice compared with the control group (p = 0.0042, 0.0036, and <0.0001 at 2, 4, and 6 weeks after COH vs. the control group, respectively). There was a significant loss of optic nerve axons in mice after intracameral injection of cross-linking hydrogel (p = 0.0095, 0.0002, and <0.0001 at 2, 4, and 6 weeks after COH vs. the control group, respectively). Conclusions: A single intracameral injection of cross-linking hydrogel can effectively induce chronic ocular hypertension in mice, which causes progressive loss of retinal ganglion cells, increased expression levels of inflammatory cytokines and microglial cell activation, and deterioration of optic nerve function.